ANALISA CEMARAN BAKTERI COLIFORM PADA SUSU KEDELAI DI PASAR TRADISIONAL SURABAYA - Nyna Rachma Kumala; Pestariati Pestariati; Wisnu Istanto (Analis Kesehatan Sains, 2021)
BSTRACTThe researcher saw that the level of cleanliness and hygiene of the sellers at traditional markets in Surabaya was still low, and the researchers also observed that the need for vegetable food was quite high. Coliformbacteria contamination in drinking water can cause various diseases such as diarrhea, fever, dysentery, andothers. The parameter is the water used for processing soy milk, namely PDAM water and refill water. Thisstudy aims to determine the presence or absence of coliform bacteria contamination in soy milk sold in thePucang market in Surabaya, as well as whether or not the soy milk is consumed. This study aims to determinethe presence or absence of coliform bacteria contamination in soy milk sold in the Pucang market in Surabaya,and whether or not the soy milk is consumed. This research used 10 samples of soy milk obtained from 10different sellers. This analysis used the MPN method with a combination of 5-1-1 tubes, and each was incubatedon Lactose Broth (LB) Single Strength, Lactose Broth Double Strength, Brilliant Green Lactose Broth (BGLB)and Eosin Methylene Blue Agar (EMBA) media. The data were presented descriptively and compared with SNI7388:2009. The results showed that 7 of 10 samples were contaminated with faecal coliform bacteria (57.14%).It can be concluded that there is coliform bacteria contamination in the sample, but the MPN value is still belowthe SNI limit.